Growth Pattern of Heifers Under Different System of Grazing on Lasiurus Sindicus Rangeland - Bawa, A K (Annals of Arid Zone, 2016)
A study to compare the effect of two grazing treatments with yearling heifers of 85-90 kg body weight, stocked at 1.5 ha/heifer on Lasilursus Eleusine dominated rangeland for five years revealed that annual weight gains ranged from 64.4 to 53 4 kg/heifer. Variations in the body weight gains were statistically non significant. Maximum body weight increase (28.1 kg/heifer) during August-Sept. and minimum (-1.3 kg/heifer) during December-January)l were statistically significant.